SOCIAL STATUS OF PHYSICAL EDUCATION TEACHERS - Mohammad Saeid Kiani; Keivan Shabani Moghaddam; leila Nazari (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
The aim of this study was to investigate the social status of physical education teachers in Hamedan province, Iran. Data gathering done by means of a researcher made questionnaire. After approving the validity by experts, the reliability approved by 11 professors through Chronbakh alpha equal to 0.87. Research society was all physical education teacher of Hamedan province consist of 800 people. The sample was estimated using Morgan table and the total number of 235 questionnaires returned and analyzed. After detecting the normal distribution of data using kolmogorov-smirnov test, independent t test and one way ANOVA were applied to test the hypothesis. A significant difference found among the mean of job interest and economic factor in samples compare to the society. In other words, teacher’s interest was higher than the average and also, the economic factors are not the main reason to choose their job. Also, significant difference found between the mean of social status of chosen jobs in sample compare to the mean of society. it means that based on respondents ideas, the social status of jobs such as seller, barber, waiter and taxi driver is lower than physical education teacher and this status is higher for physician, employee and non- physical education teacher. Totally, no matter the social status of other jobs, the credibility and status of the job of physical education teachers recognized high by respondents.